LAND MOVEMENT VULNERABILITY ZONING IN THE HILLY AREA OF NORTHERN CILACAP, CENTRAL JAVA - Nurfadli, Eza; Sukiyah, Emi; Gani, Reza Mohammad Ganjar; Ramadian, Aldrin (Faculty of Geological Engineering, Universitas Padjadjaran, 2024)
The northern part of Cilacap has an area with hilly morphology with slopes that are relatively gentle to steep. The geological setting in this region is quite complex, the combination of tectonics and the physical properties of the rocks means that this region is strongly deformed. This has an impact on areas prone to landslides as one of land movement types. To what extent can this area be classified based on the vulnerability of its land to landslides is the problem be studied. There are five aspects used in this research, namely rainfall, rock type, slope, land cover and soil type. The multi-aspect overlay method is used to determine the spatial distribution of land movement-prone zones. Geographic Information System-based software support makes the data analysis process easier. Based on the results of the spatial analysis of five aspects, it was concluded that the North Cilacap area could be grouped into 3 land movement vulnerability zones, namely the low vulnerability zone with a score of 8-17, the medium vulnerability zone with a score of 18-27, and the high vulnerability zone with a score of 28-37. The complex tectonic order is the main controller of land movement events in this region.